Feasibility study of using intravoxel incoherent motion mri to detect parotid gland abnormalities in early‐stage Sjögren syndrome patients. Issue 6 (19th November 2015) - Su, Guo‐Yi; Xu, Xiao‐Quan; Wang, Yan‐Yan; Hu, Hao; Shen, Jie; Hong, Xun‐Ning; Shi, Hai‐Bin; Wu, Fei‐Yun
Abstract : Purpose: To determine whether intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) could detect parotid gland abnormalities in Sjögren's syndrome (SS) patients who were not identified by conventional MRI. Materials and Methods: Ten consecutive patients with clinically proven SS who were not identified by conventional MRI were assessed by IVIM MRI with a 3.0T MRI scanner. Quantitative parameters (tissue diffusivity, D; pseudodiffusion coefficient, D*; perfusion fraction, f) derived from IVIM MRI were compared between the SS group and healthy control group ( n = 15). A receiver operating characteristic (ROC) curve was used to evaluate the diagnostic value of each significant parameter. Results: Excellent inter‐ and intrareader agreements were obtained during the measurement of D, f, and D* values (interreader, 0.980, 0.942, and 0.883; intrareader, 0.991, 0.952, and 0.896, respectively). All three parameters of the SS group were significantly higher than those of the healthy group (D, 1.049 ± 0.056 × 10 −3 mm 2 /s vs. 0.976 ± 0.116 × 10 −3 mm 2 /s, P = 0.012; D*, 20.410 ± 1.786 × 10 −3 mm 2 /s vs. 18.764 ± 2.433 × 10 −3 mm 2 /s, P = 0.013; f, 0.207 ± 0.003 vs. 0.182 ± 0.002, P = 0.004). ROC analysis showed that the f value had the best diagnostic performance (AUC, 0.712; Sensitivity, 0.80; Specificity, 0.57; Cutoff value, 0.185) in detecting the parotid gland abnormalities in early SS patients. Conclusion: IVIM MRI detected parotid gland abnormalities in early‐stage SS patients. J. Magn. Reson. Imaging 2016;43:1455–1461.